We travel the space ways : black imagination, fragments, and diffractions - Gunkel, Henriette; Lynch, Kara (Post-koloniale Medienwissenschaft, 2019)
A new take on Afrofuturism, this book gathers together a range of contemporary voices who, carrying legacies of 500 years of contact between Africa, Europe, and the Americas, reach towards the stars and unknown planets, galaxies, and ways of being. Writing from queer and feminist perspectives and circumnavigating continents, they recalibrate definitions of Afrofuturism. The editors and contributors of this exciting volume thus reflect on the re-emergence of Black visions of political and cultural futures, proposing practices, identities, and collectivities.